Histopathological Examination Profile of Biopsy Specimens in a Remote Tertiary Hospital - Sarker, Md Mahbur Rashid; Farooq, Md Shamim; Ansari, M Mostaque H; Hossain, Md Shahadat (KYAMC Journal, 2017)
Examination of biopsy specimens is necessary to find out the diagnosis. To detect the spectrum of histopathological findings in surgically resected specimens sent in the department of Pathology, Khwaja Yunus Ali Medical College & Hospital (KYAMCH), a rural tertiary hospital in Bangladesh. A total of 1329 specimens from January 2013 to December 2013 were evaluated in this study. Among these, 444 (33.4%) were malignant, 226 (17.0%) were benign, 29 (2.2%) were precancerous, 481 (36.2%) were inflammatory, 14 (1.1%) were tuberculosis, 12 (.9%) were suppurative lesion and 25 (1.9%) were inadequate for diagnosis. The mean age±SE of patients was 42.28±1.68 years. Incidence of malignancy was higher in compare to previous study. It indicates the importance of histopathology for diagnosis and also to exclude malignancy. So any suspicious growth should be excised as early as possible and sent for histopathology. This will help to reduce patients' morbidity and mortality. KYAMC Journal Vol. 5, No.-1, Jul 2014, Page 449-452